Correction to: Population Pharmacokinetics, Efficacy Exposure-response Analysis, and Model-based Meta-analysis of Fenebrutinib in Subjects with Rheumatoid Arthritis - Chan, Phyllis; Yu, Jiajie; Chinn, Leslie; Prohn, Marita; Huisman, Jan; Matzuka, Brett; Hanley, William; Tuckwell, Katie; Quartino, Angelica (Pharmaceutical research, 2020)
The article was published with an incomplete title. The complete title is “Population Pharmacokinetics, Efficacy Exposure-response Analysis, and Model-based Meta-analysis of Fenebrutinib in Subjects with Rheumatoid Arthritis” The original article has been corrected.